Personal reflexivity and biography: methodological challenges and strategies - Caetano, A. (2015)
This article examines the methodological device used in a sociological study that analyses empirically the concept of personal reflexivity. Taking into account the specific challenges of such an investigation the paper emphasises the potential of a biographical approach and the concrete parameters of its use. It is based on the experience of in-depth interviews conducted in more than one session and considers the different phases and elements of the empirical research process. Topics such as epistemological concerns, preparation of the interview guide, methodological cautions, the research relationship and the interview setting are at the centre of the discussion.